The experience of gestational diabetes for indigenous Māori women living in rural New Zealand: qualitative research informing the development of decolonising interventions - Reid, Jennifer (BMC Pregnancy Childbirth, 2018)
BACKGROUND: Although early detection and management of excess rates of gestational diabetes mellitus (GDM) among Indigenous women can substantially reduce maternal and offspring complications, current interventions seem ineffective for Indigenous women. While undertaking a qualitative study in a rural community in Northland, New Zealand about the complexities of living with diabetes, we observed a common emotional discourse about the burden of diabetic pregnancies. Given the significance of GDM and our commitment to give voice to Indigenous Māori women in ways that could potentially inform solutions, we aimed to explore the phenomenon of GDM among Māori women in a rural context marked by high area-deprivation. METHOD: A qualitative and Kaupapa Māori methodology was utilised. A sub-sample of women (n = 10) from a broader study designed to improve type 2 diabetes mellitus (T2DM) who had experienced GDM or pre-existing diabetes during pregnancy and/or had been exposed to diabetes in utero were interviewed. Participants in the broader study were recruited via the local primary care clinic. Experiences of GDM, in relation to their current T2DM, was sought. Narrative data was analysed for themes. RESULTS: Intergenerational experiences informed perceptions that GDM was an inevitable heritable illness that “just runs in the family.” The cumulative effects of deprivation and living with GDM compounded the complexities of participant’ lives including perceptions of powerlessness and mental health deterioration. Missed opportunities for health services to detect and manage diabetes had ongoing health consequences for the women and their offspring. Positive relationships with healthcare providers facilitated management of GDM and helped women engage with self-management. CONCLUSION: Māori women living with T2DM were clear that health providers had failed to intervene in ways that would have potentially slowed or prevented progression of GDM to T2DM. Participants revealed missed opportunities for appropriate diagnostic testing, treatment and health promotion programmes for GDM. Poor collaboration between health services and social services meant psychosocial issues were rarely addressed and the cycle of intergenerational poverty and disadvantage prevailed. These data highlight opportunities for extended case management to include whānau (family) engagement, input from social services, and evidence-based medicine and/or long-term management and prevention of T2DM. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12884-018-2103-8) contains supplementary material, which is available to authorized users.